Silicon-graphene photonic devices *Project supported by the National Major Research and Development Program (No. 2016YFB0402502), the National Natural Science Foundation of China (Nos. 11374263, 61422510, 61431166001, 61474099, 61674127), and the National Key Research and Development Program (No. 2016YFA0200200). (June 2018) - Yin, Yanlong; Li, Jiang; Xu, Yang; Tsang, Hon Ki; Dai, Daoxin
Abstract: Silicon photonics has attracted much attention because of the advantages of CMOS (complementary-metal-oxide-semiconductor) compatibility, ultra-high integrated density, etc. Great progress has been achieved in the past decades. However, it is still not easy to realize active silicon photonic devices and circuits by utilizing the material system of pure silicon due to the limitation of the intrinsic properties of silicon. Graphene has been regarded as a promising material for optoelectronics due to its unique properties and thus provides a potential option for realizing active photonic integrated devices on silicon. In this paper, we present a review on recent progress of some silicon-graphene photonic devices for photodetection, all-optical modulation, as well as thermal-tuning.